ANALISIS PENGENDALIAN KUALITAS PAKAN TERNAK PADA PROSES PELLETING DENGAN METODE STATISTICAL QUALITY CONTROL (SQC) DI PT. LEONG HUP JAYAINDO - Ari Sahputra; Margie Subahagia Ningsih; Rizkha Rida; Sanco Simanullang (Bajang Institute, 2026)
Quality plays a very important role in reducing production costs, because the lower the number of defective products, the lower the production costs incurred, which can maximize the profits obtained. One way to maintain the quality of the products produced is by establishing quality standards, as having these standards shows that the company takes full responsibility for the products they produce. The animal feed company PT. Leong Hup Jayaindo provides several types of animal feed, one of which is broiler chicken feed 9203 LH in pellet form. Not all animal feed productions are 100% successful. The daily production is 36,250 kg, and about 32 sacks experience damage. The damage standard set by the company ranges from 0.1% to 1%. Because the products produced are diverse and quality control is considered very important, the author is interested in conducting research on quality control of animal feed products using the Statistical Quality Control method.